Technology assistance for kids with learning disabilities: challenges and opportunities / Suhailah Mohd Yusof ... [et al.] - Mohd Yusof, Suhailah; Abdul Talib, Noor Hasnita; Ahmad, Jasmin Ilyani (2015)
The development of various innovative teaching-learning tools in education is increasing surprisingly due to the emergence of technology. The gratification offered by technology aided tools can increase children motivation and participation thus allowing them to retain the learning process in longer period. Children who have disability in learning are difficult to maintain their learning attentions for long time span as their brain has problems to accept; process, analyze, or keep the information. Thus, it gives difficulties for children who having this problem to learn as quickly as someone who are not affected with learning disabilities. Children with disabilities should be given the same opportunities as children who otherwise normal in terms of learning and norms. A learning disability can be mild, moderate or severe which needed different learning approach since normal learning approach does not comply with them and will hinder their learning process. Despite their different capabilities with normal children, they can also learn best through appropriate methods and approaches so that they can understand and learn to live well in the future. Therefore, one of the methods that can be used to solve this issue is by using technology tools. The opportunity in technology tools to teach and learn is believed to assist the children to face their learning challenges. Hence, the purpose of this paper is to study the concept of learning disabilities and the involvement of technology as aided tools in helping the children that have problem in their learning process. The method of writing this paper is based on the analysis of previous researches and literature reviews. The findings of this paper are the challenges of dealing with children that having learning disabilities and opportunities that can be taken to help these children. As a conclusion, this paper provides appropriate technology tools to cater several challenges faced by the children who have disabilities in learning.